Development of a quantitative measurement on visual clutter in see through display - Liu, Qingfeng; Wang, Yanyan; Bai, Yu; Yu, Mengsun; Cao, Zhengtao; Yu, Xinli; Ding, Li (Frontiers in Neuroscience, 2023)
Objective With the wide use of transmission displays to improve operation performance, the display information highlights clutter because of the contradiction between the massive amount of information and limited display area. Our study aimed to develop a quantitative measurement for declutter design and appraisal. Methods Using the ergonomics research system of characters and symbols in a see-through cockpit display, we set the simulated flight task interface at four pixel scale levels by enlarging all the display elements in a certain ratio. Flight task videos of 12 clutter degrees were recorded using each flight interface matched with three flight scene complexity levels. A total of 60 pilots completed the visual search tasks in the flight task video while the eye tracker was used to record the view path in real time. Visual search performance was analyzed to study the effect of various clutter factors and levels on pilots’ performance in visual search tasks, and acquire quantitative clutter measure parameters. Results GLM univariate test revealed that there were significant differences among the fixation time in areas of interest (AOI), total Fixation point number, total fixation time at four pixel scale levels, and three flight scene complexity levels (P < 0.05). Visual search performance declined after the cutoff point, while the clutter degree increased. According to the visual search performance data, the recommend feature congestion upper pixel number limit in a 600*800 display was 18,576, and the pixel ratio was 3.87%. Conclusion A quantitative measurement for declutter design and appraisal of cockpit displays was developed, which can be used to support see-through display design.